Service Quality, Perceived Value and Customer Satisfaction on Behavioral Intention in Restaurants: An Integrated Structural Model. Issue 4 (4th July 2021) - Tuncer, Ilhami; Unusan, Cagatay; Cobanoglu, Cihan
ABSTRACT: The objective of this study is to determine the effects of service quality, perceived value and customer satisfaction on behavioral intention. The study also introduces a new integrated structural model that combines service quality's dimensions of food quality, employee service quality, timeliness, esthetics, facility comfort and cleanliness. An explanatory and a confirmatory factor analysis was applied to develop and confirm the six-dimensional service quality scale based on data obtained from 309 customers who received service from a particular restaurant. Path analysis was also applied to examine the relationships of service quality, perceived value, and customer satisfaction with behavioral intention. The results show that service quality has a positive effect on customer satisfaction, while customer satisfaction and perceived value have positive effects on customers' behavioral intentions. In addition, other dimensions other than aesthetics have a positive role in customer satisfaction, while service quality, facility comfort and timeliness have a positive effect on perceived value. This study contributes to the service quality literature and has practical managerial implications.